Increased Nitric Oxide Production and GFAP Expression in the Brains of Influenza A/NWS Virus Infected Mice - Watanabe, Chiako (Springer US, 2007)
The cause of influenza to the brain was investigated using the A/NWS/33 influenza virus infected BALB/c mouse model. NOS-2 mRNA levels in the infected mouse brain was greater than in control mice in all brain regions examined, particularly in the olfactory bulb and hippocampus by 1 day p.i. On the contrary, no differences in NOS-1 or NOS-3 mRNA levels were found between infected and control mice. There was also a marked increase in the levels of metabolites of nitric oxide in the olfactory bulb and hippocampus. Immunohistochemistry showed positive staining for anti-NOS-2 primarily in the hippocampus of infected mice. Further, anti-NOS-2 and GFAP staining was mostly found around capillary blood vessels of the hippocampus starting early in the course of the disease. These results indicate that the NWS enhances the activation of astrocytes and NOS-2 expression which in turn enhances NO production and the expansion of capillary blood vessels.